ISLAM DAN NEGARA: Otoritas dan Kekuasaan dalam Pemikiran Islam - Syaifuddin, Helmy (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2005)
Moslem world at first only understands the concept of religious and political territory; dar al Islam and dar al harb. Since the concept of state-nation as political system entity which modernism brings has covered Islamic nation, there emerges a conceptual and historical tension on the relation between Islam and politics. The presence of state-nation which holds ethnicity as the basic criteria and foundation has taken over religious stand as the attachment of national identity. It is replaced by the emergence of sense of culture and demography as well as nationalism. The idea of state-nation has replaced the idea of Islamic order for nation. This fact leads the swift of the authority and power the leader has. Within the context of tension between Islam and politics, Muhammad Arkoun proposed the solution by redefining the concept of the authority and power. It is to accept the idea of state-nation with its secular view. He argued that political regime of Moslem world after colonialism is de facto secular and controlled by Western paradigm. Therefore, Moslem can revise the idea of secularism and the regime position committed to secularism to be Islamic-based by doing great diffusion, or what Arkoun called as intellectual modernity